Legal regulation of smart contracts in Switzerland and the United Kingdom: a comparative legal analysis - Boranbay, S.S.; Ilyassova, G.A. (Karagandy University of the name of academician E.A. Buketov, 2025)
This paper presents an analysis of the legal regulation of smart contracts in Switzerland and the United Kingdom — two leading countries in the field of digital technologies. The study examines the key approaches to the formation and execution of smart contracts, their place within the law and legislation, as well as their influence on the development of IT technologies. The central issue in regulating smart contract-related relations lies in the ambiguity of their legal nature and the lack of regulatory provisions in legislation, particularly in the Civil Code of the Republic of Kazakhstan. Special attention is given to legislative initiatives in both countries. The research shows that Switzerland has successfully integrated blockchain technologies into its legal system through the adoption of specialized legal frameworks. In contrast, the United Kingdom emphasizes the adaptation of common law to the challenges of the emerging digital economy. The article compares the two countries’ approaches in the definition and application of smart contracts, their legal status, taxation issues and data protection. In Switzerland, this is the Law on Distributed Registries (DLT Act), and in the UK, the recommendations of the Law Commission of England and Wales. The paper also focuses on security issues (cyber threats and data protection), potential risks and the cross-border use of smart contracts. A comparative analysis of both jurisdictions’ approaches is presented, along with their potential for further development, including participation in global standardization initiatives. In conclusion, the authors underscore the necessity of establishing international legal standards for the effective and secure use of smart contracts.
Швейцария мен Ұлыбританияда смарт келісім-шартын құқықтық реттеу: салыстырмалы-құқықтық талдау
Правовое регулирование смарт-контракта в Швейцарии и Великобритании: сравнительно-правовой анализ
Keywords: smart contracts; blockchain; legislation; legal regulation; Switzerland; the United Kingdom; digital economy; cross-border transactions; judicial practice; Anglo-Saxon legal system; continental legal system